Attitude towards hand eczema among hair dressers of Debre Berhan city, January 10-February 20, 2025. - Belachew Tekleyohannes Wogayehu (19470257) (2025)
Attitude towards hand eczema among hair dressers of Debre Berhan city, January 10-February 20, 2025.